The influence of water-soluble secretions of saffron seed on the germination of seeds of soft winter wheat varieties - Vira Mykolaichuk; Margaryta Korkhova (Наукові горизонти, 2023)
Due to climate change, there is a need to introduce new crops into agricultural production in Ukraine, among which Crocus sativus L., a herbaceous perennial tuberous plant, whose allopathic properties have been insufficiently studied, can take a leading place. Therefore, the aim of the study was to determine the effect of water-soluble flower secretions and their individual elements on the initial stages of seed germination of two winter durum wheat varieties (Vidrada and Koshova). In the course of the study, generally accepted methods were used: laboratory research, analysis, synthesis and statistical. It was found that water-soluble extracts of flowers of different states and elements of C. sativus flowers do not have a significant effect on the morphometric and quality parameters of wheat kernels during germination. Water-soluble secretions of flowers of different states have an inhibitory effect on the development of the root system; secretions of the bud and the bloomed flower inhibit the growth of coleoptiles. The effect of water-soluble secretions of sowing saffron flowers elements has varietal peculiarities: for winter wheat seedlings of Vidrada variety, the petals have a stimulating effect on the total length of roots and their weight; for seedlings of Koshova variety, the opposite effect is observed. The water-soluble secretions of petals and stamens have a stimulating effect on the coleoptile of Vidrada plants, and the water-soluble secretions of petals have a stimulating effect on Koshova seedlings. The correlation between the length of roots and coleoptile under the influence of watersoluble secretions of flowers of different states and their elements, as well as the index of allelopathy have varietal characteristics. The obtained scientific results will contribute to the development of agrotechnical measures for the cultivation of saffron in Ukraine, selection of winter wheat varieties for joint cultivation and use of plant residues as biological stimulants